Flowering and Fruiting of Forest Trees of Ceylon-I - Holmes, C. H. (Indian Forester, 1942)
This note refers to previous attempts made with the object of collecting reasonably dependable information on the mass flowering and fruiting of Ceylon trees and describes the procedure by which information now given has been collected and analysed. The irregularities in times of fruiting in relation to external climatic conditions exhibited by a large number of species are discussed. It is suggested that there is no real necessity to attempt to find any definite parallelism between climatic seasons and periods of flowering and fruiting in the Tropics nor to "explain" apparent irregularities on the assumption that the periodicity evident at present was determined earlier in the history of species so concerned by different climatic conditions than happen to obtain now. The chances are that periodicity of flowering and fruiting is not determined at any time by climatic variations alone and it would appear that a large number of different factors are probably responsible, the, nett resultant effects of which actually make possible the adequate perpetuation of a species despite apparent anomolousness of its behaviour as regards times of flowering and fruiting in relation to observed climatic variations.